2022
DOI: 10.1088/1755-1315/974/1/012119
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of Artemisia (Artemisia annua) extract on several concentrations and solvents

Abstract: Artemisia contains secondary metabolites with antioxidants properties. The study aimed to obtain the type and concentration of effective solvents to produce Artemisia extract with maximum antioxidant activity. The research was conducted at the Laboratory of Indonesian Spices and Medicinal Crops Research Institute in 2015. The Artemisia used for the research came from Lembang, West Java. The study was arranged in a randomized block design, 7 treatments, and 2 replications. The treatment consisted of a combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Since the values obtained in the present study are higher ( Table 1 ), we believe ethanol extraction to be more efficient than the solvents listed above. Similar results were recently communicated by Sembirin, who showed that the amount of antioxidant compounds extracted from A. annua L using an ethanol solvent was higher than the amount of antioxidant compounds extracted by a methanol solvent [ 42 ]. A higher value was also observed for the hydroalcoholic extract of A. absinthium L. from India, obtained from the aboveground parts of the plant (9.29 ± 0.51 mg GAE/g DW), as compared to hexane (0.43 ± 0.07 mg GAE/g DW) and methanol (3.55 ± 0.39 mg GAE/g DW) extracts [ 43 ].…”
Section: Discussionsupporting
confidence: 87%
“…Since the values obtained in the present study are higher ( Table 1 ), we believe ethanol extraction to be more efficient than the solvents listed above. Similar results were recently communicated by Sembirin, who showed that the amount of antioxidant compounds extracted from A. annua L using an ethanol solvent was higher than the amount of antioxidant compounds extracted by a methanol solvent [ 42 ]. A higher value was also observed for the hydroalcoholic extract of A. absinthium L. from India, obtained from the aboveground parts of the plant (9.29 ± 0.51 mg GAE/g DW), as compared to hexane (0.43 ± 0.07 mg GAE/g DW) and methanol (3.55 ± 0.39 mg GAE/g DW) extracts [ 43 ].…”
Section: Discussionsupporting
confidence: 87%
“…14 It has been widely used in china as a medical treatment as it contains secondary metabolic compounds that have antioxidant properties. 15,16 Which has attracted the attention of researchers and specialists as an effective drug against malaria. 17 It contained artemisinin and essential oil compounds.…”
mentioning
confidence: 99%